Prevalence of dental caries among 12-15 years old school children of government and private schools in Agra City - Ankita Bansal; Navpreet Kaur; Pramod Kumar Yadav; Vivek Kumar Sharma; Prateek Jain; Gaurav Agrawal (Wolters Kluwer Medknow Publications, 2020)
Background: Oral health is an important component of general health, with dental caries affecting a person's ability to eat, speak, or socialize. Dental caries is one of the most prevalent diseases affecting human beings and persists till date as a challenge to the medical and dental profession in particular and the society in general. Aim: The study aims to assess the prevalence of dental caries among 12-15-years-old school-going children of government and private schools in Agra city, Uttar Pradesh, India. Materials and Methods: A crosssectional study was conducted among 12-15-years-old school-going children of government and private schools in Agra city, Uttar Pradesh, India. A total of 1600 school children were through a multistage random sampling procedure. The children were examined according to the World Health Organization criteria, 2013. Information regarding a patient's demographic profile was recorded using a self-administered questionnaire. Chi-square test was used to find the significance of study parameters. The level of significance (P value) was fixed at 0.05. Results: The present study reveals a prevalence of dental caries was almost of the same magnitude in the 12 and 13 years of age group, and it was found to be 28.6% and 28.9%, respectively among government and private school children. It was found that among 14 and 15 years of age groups, dental caries affected 22.9% and 19.6% of the study participants, respectively from both government and private school children. The results were found to be highly statistically significant between government and private school children regarding the number of carious teeth. Conclusion: The prevalence of dental caries was found to be the major public health problem among both the government and private school children of Agra city, which need immediate attention. Therefore, there is a need to develop preventive and promotional oral health strategies to combat this disease.